Method for detecting trace nano plastic in biological fluid through combination of magnetic solid-phase extraction and surface enhanced Raman spectroscopy

Through the combination of magnetic solid phase extraction and surface-enhanced Raman spectroscopy, the problem of trace nanoplastic detection in humans is solved, and the detection effect of high sensitivity and high reproducibility is achieved.

CN119534419APending Publication Date: 2025-02-28CAPITAL UNIVERSITY OF MEDICAL SCIENCES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411582485.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively detect trace nanoplastics in human body, mainly due to their small size, low concentration and complex biological matrix, which makes it difficult to detect.

Method used

The biological fluid samples were enriched by amino acid beads and detected using a surfactant-free SERS-enhanced substrate using magnetic solid phase extraction combined with surface-enhanced Raman spectroscopy (SERS).

Benefits of technology

It realizes qualitative and quantitative analysis of trace nanoplastics in biological fluids, and has the advantages of simple operation and good reproducibility, low detection limit and strong quantitative analysis ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119534419A_ABST
    Figure CN119534419A_ABST
Patent Text Reader

Abstract

The invention relates to a method for detecting trace nano plastic in biological fluid by combining magnetic solid-phase extraction and surface enhanced Raman spectroscopy. The method for detecting the trace nano plastic in the biological fluid by combining the magnetic solid-phase extraction and the surface enhanced Raman spectroscopy comprises the following steps: enriching the nano plastic in a biological fluid sample by using aminated magnetic beads to obtain an aggregate, and desorbing the aggregate to obtain a desorption solution, and mixing the desorption solution with an SERS enhanced substrate solution, drying and detecting. According to the method, the strong enrichment capacity of the aminated magnetic beads and the excellent performance of the SERS enhanced substrate are combined, qualitative and quantitative analysis of trace multi-size nano plastic in biological fluid is achieved, and the method has the advantages of being easy to operate, high in reproducibility and the like. The detection limit of polystyrene nano plastic in urine and serum is as low as 6 * 10 <-7 > g / L, and the quantitative analysis capability is strong (R2gt; and the standard addition recovery rate in urine and serum is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biological fluid pollutant detection, and specifically relates to a method for detecting trace nanoplastics in biological fluids by combining magnetic solid phase extraction and surface enhanced Raman spectroscopy. Background Art

[0002] With the continuous detection of microplastics (MPs) and nanoplastics (NPs) in human body fluids and organs, their potential health risks have attracted widespread attention worldwide. A large number of toxicity studies have shown that NPs have a higher biological toxicity than microplastics due to their larger specific surface area. NPs that enter the animal body can penetrate biological barriers and accumulate in multiple tissues and organs (especially the brain and reproductive organs), showing higher biological toxicity. Studies have found that 500nm NPs have a significantly higher inflammatory effect on zebrafish than 50μm NPs. Although there is increasing evidence showing the prevalence of NPs and the associated toxicity risks, there are still many bottlenecks in achieving accurate quantification of NPs in the human body due to their small size, low concentration, and complex biological matrix.

[0003] At present, methods for enrichment and impurity removal of NPs include membrane filtration, ultrafiltration, ultracentrifugation, turbidity point extraction and solvent evaporation. However, these methods still face challenges in terms of anti-interference ability and environmental pollution. In contrast, magnetic nanoparticles have attracted widespread attention due to their advantages such as simple operation, high enrichment efficiency and low energy consumption. The significant advantage of magnetic nanoparticles is that they are easy to functionalize and can selectively adsorb specific pollutants. Considering the hydrophobic properties of plastics, magnetic nanoparticles have often been modified with hydrophobic ligands in recent years to enhance their adsorption capacity for NPs. However, these hydrophobic ligands may result in poor dispersibility in water, high production costs and difficulty in regeneration, leading to secondary pollution.

[0004] Surface enhanced Raman spectroscopy (SERS) is a powerful technique for rapid detection of trace samples in complex matrices, and its unique Raman "fingerprint" signal can be used to identify specific analyte molecules. The enhancement of SERS relies on the localized surface plasmon resonance effect of noble metal nanoparticles. However, the sensitivity of existing technologies in detecting NPs is still low. Traditional methods usually rely on salts to promote the aggregation of NPs with substrates, but uncontrolled aggregation can lead to poor reproducibility of SERS detection. In addition, the use of surfactants to control the morphology and stability of the substrate will hinder the analyte molecules from approaching the surface of gold nanoparticles and increase the biological toxicity of the material. Therefore, it is crucial to develop a surfactant-free SERS substrate that can produce ultra-high SERS signals and good reproducibility without the addition of salts. Summary of the invention

[0005] The purpose of the present invention is to provide a method for detecting trace nanoplastics in biological fluids by combining magnetic solid phase extraction and surface enhanced Raman spectroscopy to solve the technical problem that the detection of nanoplastics in the human body is difficult to achieve due to the small size of nanoplastics, low concentration in the human body, and complex biological matrix.

[0006] In order to achieve the above purpose, the technical solution adopted by the present invention is:

[0007] A method for detecting trace nanoplastics in biological fluids by combining magnetic solid phase extraction and surface enhanced Raman spectroscopy, comprising the following steps: using amino magnetic beads to enrich biological fluid samples containing nanoplastics to obtain aggregates, desorbing the aggregates to obtain desorption liquid, mixing the desorption liquid with a SERS enhanced substrate solution, drying, and detecting.

[0008] Furthermore, the biological fluid is urine or serum, and the concentration of nanoplastics in the biological fluid sample is 6×10 -7 -6×10 -3 g / L.

[0009] Furthermore, the diameter of the nanoplastic is 20-200 nm.

[0010] Furthermore, the concentration of the amino-modified magnetic beads in the biological fluid sample is 1.5-2 g / L.

[0011] Furthermore, the desorption of the agglomerates is performed by adding an eluent to the agglomerates and performing desorption under ultrasound; the eluent is a methanol-acetic acid mixed solution or a methanol-ammonia aqueous solution; the volume ratio of methanol to acetic acid in the methanol-acetic acid mixed solution is 9:1-1:1; the volume ratio of methanol to ammonia aqueous solution in the methanol-ammonia aqueous solution is 9:1-1:1.

[0012] Furthermore, the volume ratio of the SERS enhancement substrate solution to the desorption solution is 1:4-2:1.

[0013] Furthermore, the preparation method of the amino magnetic beads is: 3 O 4 @SiO 2 Add polyethyleneimine solution to the powder and shake it; every 50 mg of Fe 3 O 4 @SiO 2 The powder corresponds to 300-400 mg of polyethyleneimine.

[0014] Furthermore, the method for preparing the SERS enhanced substrate solution comprises the following steps:

[0015] S1: preparing a gold nanostar solution: preparing a gold seed solution; adding 100-200 μL of the gold seed solution to a mixed solution containing 10-20 mL of 1-2 mM tetrachloroauric acid and 40-80 μL of 1-2 M hydrochloric acid, adding 400-800 μL of 3-6 mM silver nitrate solution, and 200-400 μL of 100-200 mM ascorbic acid solution to obtain a gold nanostar solution;

[0016] S2: adding 8.6-9.8 mL of a second silver nitrate solution with a concentration of 0.3-2.5 mM and 0.2-1.4 mL of a second ascorbic acid solution with a concentration of 80-120 mM to the gold nanostar solution to obtain a solution containing silver-coated gold nanostars;

[0017] S2: 12-15 mL of the solution containing silver-coated gold nanostars is mixed with 12-15 mL of 2.5-5 mg / mL polyethyleneimine solution, followed by sonication, centrifugation, and resuspending.

[0018] Furthermore, when the biological fluid is serum, the serum needs to be mixed with potassium hydroxide, heated in a water bath and diluted before adding the nanoplastic.

[0019] Beneficial effects of the present invention:

[0020] The present invention uses amino magnetic beads (Fe 3 O 4 @SiO 2 The strong enrichment ability of @PEI) combined with the excellent performance of SERS enhanced substrates realizes the qualitative and quantitative analysis of trace multi-sized NPs in biological fluids, with the advantages of simple operation and high reproducibility. The detection limit of polystyrene nanoplastics (PS NPs) in urine and serum is as low as 6×10 -7 g / L, strong quantitative analysis capability (R 2 >0.982), and the spiked recoveries in urine and serum were excellent. This method provides strong technical support for tracking the internal exposure of NPs and evaluating the potential health hazards in the human body.

[0021] Fe of the present invention 3 O 4 @SiO 2 @PEI enriches and separates NPs in biological fluids through electrostatic interaction, hydrophobic interaction, hydrogen bonding and π-π interaction, and has stronger anti-interference ability. 3 O 4 @SiO 2 @PEI is highly reusable and maintains excellent enrichment performance after multiple uses, which is green and environmentally friendly.

[0022] The present invention develops a SERS enhancement substrate without surfactant and with a large number of intra-particle hot spots, which promotes the co-adsorption of NPs and the SERS enhancement substrate in the hot spots. Compared with the method of introducing external reagents to promote the aggregation of nanoparticles in the prior art, the sample preparation process is simplified. The surfactant-free synthesis method also reduces the biological toxicity of the SERS enhancement substrate, while also improving the stability of the SERS enhancement substrate and the reproducibility and sensitivity of the method. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Fe 3 O 4 @SiO 2 @The effect of PEI concentration in the sample solution on the enrichment efficiency of PS NPs;

[0024] Figure 2 To prepare Fe 3 O 4 @SiO 2 Effect of concentration of polyethyleneimine solution on Fe 3 O 4 @SiO 2 @Effect diagram of PEI enrichment of PSNPs;

[0025] Figure 3 Fe 3 O 4 @SiO 2 @TEM images of PS NPs of different sizes adsorbed on PEI, where A is 20 nm, B is 100 nm, C is 200 nm, and D is a mixture of 20, 100, and 200 nm;

[0026] Figure 4 Different eluents induce Fe aggregates 3 O 4 @SiO 2 @Analysis efficiency diagram of desorption of PS NPs by PEI-PS NPs;

[0027] Figure 5 Fe 3 O 4 @SiO 2 @The effect of PEI repetition times on PS NPs enrichment efficiency;

[0028] Figure 6 The figure shows the effect of the concentration of silver nitrate solution II and the modification of polyethyleneimine on the SERS enhancement performance;

[0029] Figure 7 The effect of different volume ratios of BGNS-Ag3-PEI and analytical solution on the SERS performance when detecting PS NPs;

[0030] Figure 8 SERS spectra of PS NPs, a mixture of PS NPs and BGNS-Ag3, a mixture of PS NPs, BGNS-Ag3 and NaI, and a mixture of PS NPs and BGNS-Ag3-PEI at the same PS NPs concentration;

[0031] Fig. 9 15 points were randomly selected from the mixture of PS NPs, BGNS-Ag3, NaI and the mixture of PS NPs and BGNS-Ag3-PEI. The PS NPs were detected at 1002 cm -1 Intensity variation diagram at the characteristic peak, where A is the mixture of PS NPs, BGNS-Ag3, and NaI, and B is the mixture of PS NPs and BGNS-Ag3-PEI;

[0032] Fig.10 TEM images of BGNS-Ag3-PEI adsorbing PS NPs of different sizes, where A is 20 nm, B is 100 nm, and C is 200 nm;

[0033] Fig.11 The stability change diagram of BGNS-Ag3 and BGNS-Ag3-PEI from 0 to 3 weeks, where A is BGNS-Ag3 and B is BGNS-Ag3-PEI;

[0034] Fig.12 Schematic diagram of the process of detecting trace PS NPs in biological fluids by magnetic solid phase extraction-surface enhanced Raman spectroscopy;

[0035] Fig.13 Raman spectra and spike recovery rates for detecting PS NPs in urine and serum. DETAILED DESCRIPTION

[0036] Fe 3 O 4 @SiO 2 From Science Compass.

[0037] The present invention will be further described below in conjunction with the embodiments of the present invention and the accompanying drawings.

[0038] Example 1

[0039] Aminated magnetic beads (Fe 3 O 4 @SiO 2 The preparation method of the SERS enhanced substrate comprises the following steps:

[0040] 1. Fe3 O 4 @SiO 2 Preparation of @PEI

[0041] To 50mg, 230nm Fe 3 O 4 @SiO 2 Add 10 mL of 40 mg / mL polyethyleneimine (PEI) solution to the powder and shake for 12 h to obtain Fe 3 O 4 @SiO 2 @PEI, rinsed with deionized water 3 times, rinsed with ethanol 3 times, and finally dispersed in 10mL deionized water to obtain Fe 3 O 4 @SiO 2 @PEI solution, stored at 4℃.

[0042] 2. Preparation of Gold Nanostars (GNS)

[0043] Under vigorous stirring, 1.5 mL of 1% citrate solution was added to 10 mL of boiling 1 mM HAuCl 4 (tetrachloroauric acid) and continued boiling for 10 min to obtain a transparent wine-red gold seed solution. Subsequently, 100 μL of the gold seed solution was added to a 10 mL, 1 mM HAuCl 4 and 40 μL of 1M HCl mixed solution, stirred for 2 min. Add 400 μL of 3 mM silver nitrate solution 1, after an interval of 5 s, add 200 μL of 100 mM ascorbic acid solution 1, stirred for 2 min, and the GNS solution was obtained.

[0044] 3. Preparation of silver-coated gold nanostars (BGNS-Ag)

[0045] 8.6 mL of 2.5 mM silver nitrate solution II and 1.4 mL of 100 mM ascorbic acid solution II were added to the GNS solution and stirred for 2 min. The color of the solution quickly changed to blue-black to obtain a solution containing silver-coated gold nanostars. The solution containing silver-coated gold nanostars was named BGNS-Ag3.

[0046] 4. Preparation of Polyethyleneimine-modified Silver-coated Gold Nanostars (BGNS-Ag-PEI)

[0047] Take 5mL of the solution containing silver-coated gold nanostars and add it to 5mL of PEI solution 2 (5mg / mL), mix well and place it in an ultrasonic cleaner for 15min of intense ultrasound. Immediately centrifuge the solution to remove the unreacted PEI solution, resuspend it in deionized water to obtain the SERS enhanced substrate solution, and store it at 4°C. The thickness of the PEI layer is 2nm. The SERS enhanced substrate is named BGNS-Ag3-PEI.

[0048] Example 2

[0049] The method for detecting trace amounts of PS NPs in biological fluids by magnetic solid phase extraction-surface enhanced Raman spectroscopy of Example 2 comprises the following steps:

[0050] PS NPs with particle sizes of 20 nm, 100 nm, 200 nm, and mixed (20 nm, 100 nm, 200 nm) were spiked into urine to obtain urine samples at a spike concentration of 6 × 10 -6 g / L. Take 10mL urine sample and add Fe 3 O 4 @SiO 2 @PEI, maintained continuous oscillation at 80 rpm at room temperature, 3 O 4 @SiO 2 @PEI is in full contact with PS NPs, and the formed aggregates are collected by magnets. 3 O 4 @SiO 2 @PEI-PS NPs and discard the supernatant. Add 40 μL methanol-acetic acid solution to induce Fe 3 O 4 @SiO 2 The desorption liquid was obtained by desorption of @PEI-PS NPs, and the desorption liquid was mixed with 40 μL BGNS-Ag3-PEI solution to obtain a mixture, which was dropped onto tin foil, placed in an oven for drying, and then directly used for SERS measurement. The detection flow chart is shown in Fig.12 As shown, from Fig.12 and Fig.13 It can be seen that at 6×10 -6 The fingerprint of PS NPs in urine at 1002 cm -1 The spiked recoveries were all above 89.8%, which proved that this method can achieve accurate quantitative analysis of PS NPs in urine. 3 O 4 @SiO 2 @The concentration of PEI in the sample solution is 1.5 g / L.

[0051] Fe of Example 23 O 4 @SiO 2 @PEI uses the Fe prepared in Example 1 3 O 4 @SiO 2 @PEI. The BGNS-Ag3-PEI solution in Example 2 used the BGNS-Ag3-PEI solution prepared in Example 1.

[0052] Example 3

[0053] The method for detecting trace amounts of PS NPs in biological fluids by combining magnetic solid phase extraction and surface enhanced Raman spectroscopy of Example 3 comprises the following steps:

[0054] Serum was mixed with 10% KOH in a volume ratio of 1:1, incubated at 80 °C for 4 h, and diluted 100 times with deionized water to reduce viscosity and interference from biomolecules. Then, PS NPs with sizes of 20 nm, 100 nm, 200 nm, and mixed sizes (20 nm, 100 nm, and 200 nm) were added to obtain serum samples. The spiked concentration was 6 × 10 -6 Take 10mL of serum sample and add 1.5g / L of Fe 3 O 4 @SiO 2 @PEI, maintained continuous oscillation at 80 rpm at room temperature, 3 O 4 @SiO 2 @PEI was fully contacted with PSNPs, and the formed aggregates were collected with a magnet and the supernatant of the solution was discarded. 40 μL of methanol-acetic acid solution was added to induce the desorption of the aggregates, and the desorbed solution was mixed with 40 μL of BGNS-Ag3-PEI solution to obtain a mixture, which was dripped onto tin foil, placed in an oven for drying, and directly used for SERS measurement. Fig.12 and Fig.13 As shown, in 6×10 -6 The fingerprint of PS NPs in serum at 1002 cm -1 The recoveries of the spiked samples were all above 85.8%, which proved that the method achieved the accurate quantitative analysis of PS NPs in serum.

[0055] Fe of Example 3 3 O 4 @SiO 2 @PEI uses the Fe prepared in Example 1 3 O 4 @SiO 2@PEI. The BGNS-Ag3-PEI solution in Example 3 used the BGNS-Ag3-PEI solution prepared in Example 1.

[0056] Example 4

[0057] The preparation method of the SERS enhanced substrate in Example 4 is substantially the same as that in Example 1. The difference between the SERS enhanced substrate in Example 4 and Example 1 is that the concentration of the silver nitrate solution II added during the preparation of the silver-coated gold nanostars in Example 4 is 0.3 mM, and is named BGNS-Ag1.

[0058] Example 5

[0059] The preparation method of the SERS enhanced substrate in Example 5 is substantially the same as that in Example 1. The difference between the SERS enhanced substrate in Example 5 and Example 1 is that the concentration of the silver nitrate solution 2 added during the preparation of the silver-coated gold nanostars in Example 5 is 0.8 mM, and is named BGNS-Ag2.

[0060] Experimental Example 1

[0061] PS NPs with a particle size of 100 nm were added to deionized water to prepare a 0.3 g / L PS NPs dispersion. 3 O 4 @SiO 2 @PEI was added to 10 mL of PS NPs dispersion, Fe 3 O 4 @SiO 2 The concentrations of @PEI in the sample solutions were 0.5, 1.0, 1.2, 1.5, and 2.0 g / L, respectively. The Fe 3 O 4 @SiO 2 @PEI is in full contact with PS NPs. The aggregates formed by Fe 3 O 4 @SiO 2 @PEI-PS NPs, extract the supernatant and the solution before adsorption, use a UV-visible spectrophotometer at a wavelength of 230nm, and calculate the adsorption rate by measuring the absorbance of the residual PS NPs in the supernatant and the solution before adsorption. The results are shown in Figure 1 As shown, from Figure 1 It can be seen that the extraction efficiency of PS NPs increases with the increase of Fe 3 O 4 @SiO 2 @PEI content gradually increased, and Fe 3 O 4 @SiO 2The concentration of @PEI of 1.5 g / L was sufficient to completely extract PS NPs, with an adsorption rate of 98.6%.

[0062] Experimental Example 2

[0063] PS NPs with particle sizes of 20 nm, 100 nm, 200 nm and mixed particle sizes (20 nm, 100 nm, 200 nm) were added to deionized water to prepare four PS NP dispersions with a concentration of 0.1 g / L. 1.5 g / L of Fe was added to 10 mL of the PS NP dispersion. 3 O 4 @SiO 2 @PEI, maintained continuous oscillation at 80 rpm at room temperature, 3 O 4 @SiO 2 @PEI is in full contact with PS NPs. The aggregates formed at the bottom of the container were collected by a permanent magnet and resuspended in deionized water for dispersion. Fe 3 O 4 @SiO 2 @PEI adsorption on NPs of various sizes. Figure 3 As shown, transmission electron microscopy observations show that Fe 3 O 4 @SiO 2 @PEI can act as a connector for NPs and can effectively adsorb multi-scale PS NPs to form aggregates. The smallest PS NPs of 20 nm can also be effectively enriched.

[0064] Experimental Example 3

[0065] The aggregates formed in Experimental Example 2 were collected, and eluent (urea, ethanol, sodium hydroxide, hydrochloric acid, a methanol-acetic acid mixed solution with a volume ratio of 7:3 or a methanol-ammonia mixed solution with a volume ratio of 7:3) was added. After mixing, they were placed in an ultrasonic cleaner and subjected to intense ultrasound to induce desorption. The ultraviolet-visible spectrum of the supernatant was collected to track and calculate the Fe 3 O 4 @SiO 2 @PEI desorption rate. Collect the desorbed Fe 3 O 4 @SiO 2 @PEI, and washed with deionized water and anhydrous ethanol several times to remove the residual plastic microspheres and impurities. 3 O 4 @SiO 2 @PEI re-coats PEI for the next round of use, Fe 3 O 4 @SiO 2@PEI was recycled 5 times and all experiments were repeated 3 times.

[0066] The results are as follows Figure 4 As shown, the induction efficiency of various desorption solutions indicates that Fe 3 O 4 @SiO 2 The adsorption of @PEI on PS NPs is promoted by electrostatic, hydrophobic, hydrogen bonding and π-π interactions. The effect of pH was studied by adding NaOH or HCl. At high pH, ​​some Fe 3 O 4 @SiO 2 @PEI has a negative charge, which leads to mutual repulsion with PS NPs. 3 O 4 @SiO 2 @PEI is positively charged, while PS NPs are close to charge neutrality, resulting in no electrostatic attraction, thus inducing partial desorption. Ethanol was added to the desorption solution to probe the hydrophobic interaction, and about 65% of the desorption occurred. It is speculated that the hydrophobic benzene ring structure of PS NPs interacts with the hydrophobic -CH 2 -group interaction. Urea acts as a hydrogen bond disruptor, and the addition of urea produces about 62% of the desorption, indicating that hydrogen bonding plays an important role. The CH bonds on PS NPs act as donors to Fe 3 O 4 @SiO 2 The N atoms on PEI may act as receptors and hydrogen bonds may occur. FTIR spectroscopy confirmed that PEI is a polymer containing nitrogen atoms, which can provide π-electron functional groups to interact with the benzene rings of PS NPs through π-π interactions. The mixed solutions of methanol-acetic acid and methanol-ammonia water solution had the best desorption effect, with a desorption rate of more than 94%.

[0067] The high desorption rate proves that Fe 3 O 4 @SiO 2 @PEI can be regenerated and reused, and the reuse efficiency is as Figure 5 As shown in Figure 5, after 5 adsorption-desorption cycles, the removal efficiency of PS NPs did not decrease significantly and remained above 90.4%.

[0068] Experimental Example 4

[0069] BGNS-Ag1, BGNS-Ag2 and BGNS-Ag3 were mixed with 200 nm PS NPs to obtain three mixtures. The three mixtures were dropped onto tin foil, dried in an oven and subjected to SERS measurement. The SERS peaks at 1002 cm -1 The intensity changes of PSNPs characteristic peaks at .

[0070] from Figure 6 It can be seen that with the increase of the concentration of silver nitrate solution II, the thickness of the silver layer gradually increases, and the SERS enhancement effect of BGNS-Ag3 is the best.

[0071] Experimental Example 5

[0072] PS NPs with a size of 200 nm were selected, and the SERS enhanced substrate solution (BGNS-Ag3-PEI) and the analyzed sample solution obtained after enrichment were mixed in a volume ratio of 1:4, 1:2, 3:4, 1:1, and 2:1 to prepare 5 samples to be tested. The SERS signals of the 5 samples to be tested were collected by Raman spectrometer and the 1002 cm -1 Changes in the intensity of the characteristic peaks of PS NPs at .

[0073] from Figure 7 It can be seen that when there is too little BGNS-Ag3-PEI, it is not enough to generate enough hot spots and cannot fully enhance the Raman signal of the sample molecules. On the contrary, when an excessive amount of BGNS-Ag3-PEI is added, too many NPs will be adsorbed on the surface of BGNS-Ag3-PEI, resulting in the formation of larger aggregates and precipitation into an uneven solution, which is not conducive to Raman signal detection. Therefore, the best enhancement effect can only be achieved when BGNS-Ag3-PEI and PS NPs are kept in an appropriate ratio. When the volume ratio is 1:1, the characteristic peak intensity of PS NPs reaches the maximum, and the best detection effect is obtained.

[0074] Experimental Example 6

[0075] 200 nm PS NPs were selected as the model. At the same PS NPs concentration, PS NPs were mixed with BGNS-Ag3, PS NPs, BGNS-Ag3, and coagulant NaI were mixed, and PS NPs were mixed with BGNS-Ag3-PEI to prepare the test samples. The 1002 cm -1 The change of SERS intensity at the sample point was studied, and 15 different sample points were randomly selected to further study the repeatability of SERS measurement results of different mixed samples. Transmission electron microscopy was used to observe the adsorption of PS NPs of different sizes (20nm, 100nm, 200nm) on BGNS-Ag3-PEI.

[0076] The aggregation of nanoparticles can significantly enhance the SERS signal. Figure 8 It can be seen that after the introduction of the coagulant NaI, although the aggregated BGNS-Ag3 enhanced the signal of PS NPs to a certain extent, the uncontrolled aggregation would lead to uneven signal distribution ( Fig. 9). The BGNS-Ag-PEI synthesized in the present invention can produce the strongest and most stable Raman signal without the need for surfactants. Compared with BGNS-Ag3 with the addition of NaI to promote coagulation, the selective co-adsorption based on BGNS-Ag3-PEI has higher repeatability in SERS detection, with a relative standard deviation (RSD) of 4.8%, and the SERS intensity is almost 3 times higher, which indicates that the 2nm PEI shell plays a vital role in the adsorption and enrichment of NPs. Fig.10 It can be seen that BGNS-Ag3-PEI can effectively adsorb multi-scale PS NPs of 20, 100 and 200 nm, and there are two distinct adsorption forms. For nanoparticles smaller than BGNS-Ag3-PEI, one BGNS-Ag3-PEI will adsorb multiple nanoparticles. When the size of NPs increases to 200 nm, BGNS-Ag3-PEI tends to adsorb on the surface of NPs, ensuring the effective adsorption of BGNS-Ag3-PEI on nanoparticles of different sizes.

[0077] Experimental Example 7

[0078] The BGNS-Ag3 solution and the BGNS-Ag3-PEI solution were placed at room temperature for three weeks, and their physical state changes were observed. The changes in their UV characteristic peaks were measured using a UV-visible spectrophotometer.

[0079] like Fig.11 As shown in the figure, after one week at room temperature, the color of the BGNS-Ag3 solution changed from dark blue to dark green, and agglomeration and deposition occurred after three weeks. At the same time, the characteristic peak of the ultraviolet absorption peak of BGNS-Ag3 disappeared after a significant blue shift. In contrast, the BGNS-Ag3-PEI solution did not show obvious stratification, remained in a homogeneous state, and its ultraviolet absorption peak did not change significantly. The above results show that the modification of PEI significantly improves the dispersibility of BGNS-Ag3, solves the shortcomings of insufficient stability of BGNS-Ag3 itself, and provides effective sites for the subsequent adsorption of PS NPs.

Claims

1. A method for detecting trace amounts of nanoplastics in biological fluids by magnetic solid phase extraction-surface enhanced Raman spectroscopy, characterized in that: The following steps are involved: Aminated magnetic beads are used to enrich biological fluid samples containing nanoplastics to obtain aggregates, and the aggregates are desorbed to obtain desorption liquid, which is mixed with a SERS enhanced substrate solution and then dried and detected.

2. The method for detecting trace amounts of nanoplastics in biological fluids by magnetic solid phase extraction-surface enhanced Raman spectroscopy according to claim 1, characterized in that: The biological fluid is urine or serum, and the concentration of nanoplastics in the biological fluid sample is 6×10 -7 -6×10 -3 g / L.

3. The method for detecting trace amounts of nanoplastics in biological fluids by magnetic solid phase extraction-surface enhanced Raman spectroscopy according to claim 2, characterized in that: The diameter of the nano plastic is 20-200nm.

4. The method for detecting trace amounts of nanoplastics in biological fluids by magnetic solid phase extraction-surface enhanced Raman spectroscopy according to claim 1, characterized in that: The concentration of the amino-modified magnetic beads in the biological fluid sample is 1.5-2 g / L.

5. The method for detecting trace amounts of nanoplastics in biological fluids by magnetic solid phase extraction-surface enhanced Raman spectroscopy according to claim 1, characterized in that: The desorption of the agglomerates is performed by adding an eluent to the agglomerates and performing desorption under ultrasound; the eluent is a methanol-acetic acid mixed solution or a methanol-ammonia water mixed solution; the volume ratio of methanol to acetic acid in the methanol-acetic acid mixed solution is 9:1-1:1; the volume ratio of methanol to ammonia water in the methanol-ammonia water mixed solution is 9:1-1:

1.

6. The method for detecting trace amounts of nanoplastics in biological fluids by magnetic solid phase extraction-surface enhanced Raman spectroscopy according to claim 1, characterized in that: The volume ratio of the SERS enhancement substrate solution to the desorption liquid is 1:4-2:

1.

7. The method for detecting trace amounts of nanoplastics in biological fluids by magnetic solid phase extraction-surface enhanced Raman spectroscopy according to claim 1, characterized in that: The preparation method of the amino magnetic beads is as follows: adding polyethyleneimine solution to Fe3O4@SiO2 powder and shaking; every 50 mg of the Fe3O4@SiO2 powder corresponds to 300-400 mg of polyethyleneimine.

8. The method for detecting trace nanoplastics in biological fluids by magnetic solid phase extraction-surface enhanced Raman spectroscopy according to claim 1, characterized in that: The method for preparing the SERS enhanced substrate solution comprises the following steps: S1: preparing a gold nanostar solution: preparing a gold seed solution; adding 100-200 μL of the gold seed solution to a mixed solution containing 10-20 mL of 1-2 mM tetrachloroauric acid and 40-80 μL of 1-2 M hydrochloric acid, and then adding 400-800 μL of 3-6 mM silver nitrate solution, and 200-400 μL of 100-200 mM ascorbic acid solution to obtain a gold nanostar solution; S2: adding 8.6-9.8 mL of a second silver nitrate solution with a concentration of 0.3-2.5 mM and 0.2-1.4 mL of a second ascorbic acid solution with a concentration of 80-120 mM to the gold nanostar solution to obtain a solution containing silver-coated gold nanostars; S2: 12-15 mL of the solution containing silver-coated gold nanostars is mixed with 12-15 mL of 2.5-5 mg / mL polyethyleneimine solution, followed by sonication, centrifugation, and resuspending.

9. The method for detecting trace nanoplastics in biological fluids by magnetic solid phase extraction-surface enhanced Raman spectroscopy according to claim 2, characterized in that: When the biological fluid is serum, the serum needs to be mixed with potassium hydroxide, heated in a water bath and diluted, and then the nanoplastic is added.

Citation Information

Patent Citations

  • Composition and method for preparing epoxy urethanic adhesive

    BG40069A1